FATORES QUE AFETAM A COMUNIDADE DE ROEDORES (MAMMALIA) EM AMBIENTE PERI-URBANIZADO - Rodrigues, Marina Falcão; Moraes, Barbara Lins Caldas de; Oliveira, Maria Adélia Borstelman de; Leite, Luzinalva Mendes Revorêdo Mascarenhas (Revista Nordestina de Zoologia, 2011)
Human activity has increasingly brougth negative effects of difficult predictability to natural ecosystems. Among them, the most impacting are the expasion and estabilishment of urban conglomerates. The campus of Federal Rural University of Pernambuco (UFRPE) is inserted within an urban area which contains clusters of Atlantic Forest Conglomerates, linked to Dois Irmãos State Park. The present study aimed to obtain ecological data on rodents community from UFRPE, identifying factors that can affect them. In order to achieve the results, the work was carried out in four different areas, between June and November of 2004 using two estrategies: documental research, achieved by means of interviews; and field collections, by means of the capture-mark-release methods. From the field collection data, the rodent species registered were Rattus norvegicus and Cavia sp. For R. norvegicus it was estimated the capture success (2.65%), the population density (24.49 ind/ha), the relative abundance (0.843) and the analysis of the seasonality relation with reproduction and body mass. Other rodents, as Hydrochoerus hydrochaeris, Sciurus sp., Coendou sp. and Cuniculus paca, were identified using questionnaires. It was also observed the presence of anthropic activities as hunting, deforestation and burning, which bring negative ecological consequences for the rodents community. It urges, therefore, to implement measures aimed at the conservation of local biodiversity.